2019
DOI: 10.3390/md17120692
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Oligosaccharides Affect Mechanical Properties and Antifungal Activity of Alginate Buccal Films with Posaconazole

Abstract: Sodium alginate and its oligosaccharides through potential antifungal properties might improve the activity of antifungal drugs enhancing their efficacy and potentially reducing the frequency of application. Mucoadhesive buccal films are oral dosage forms designed for maintaining both local or systemic drug effects and seem to be a very promising alternative to conventional oral formulations. Hence, in this study, mucoadhesive buccal films based on the alginate and its oligosaccharide oligomer composed predomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…The mobile phase was applied with the flow rate 0.5 mL/min. UV detection was achieved at a wavelength of 280 nm [ 23 ]. POS retention time was recorded at 5.5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The mobile phase was applied with the flow rate 0.5 mL/min. UV detection was achieved at a wavelength of 280 nm [ 23 ]. POS retention time was recorded at 5.5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Mucoadhesive properties of the films were assessed with Texture Analyzer TA.XT. Plus (Stable Microsystems, Godalming, UK), according to the previously optimized method [46]. For that purpose, 4 cm 2 films were placed on the mucoadhesion ring A/Muc and moisturized with 250 µL of the SS pH 6.8.…”
Section: Determination Of Mucoadhesivenessmentioning
confidence: 99%
“…Considering the potential effect of the freezing process on the buccal mucosa integrity, we tried to minimize the effect of storage conditions on the measurement's variations according to the previous attempts performed by our research group [46,48]. For that purpose, the buccal mucosa was carefully selected in order to eliminate potential differentiations arising from inhomogeneity of the mucosal surface.…”
Section: Mucoadhesive Propertiesmentioning
confidence: 99%
“…The oligosaccharide (DP > 8) appeared at the initial stage of the degradation process and may be applied in the development of a novel drug carrier. Several reports suggested that AOS with higher polymerization could play a dual role (effector and carrier) in drug delivery systems, showing obvious advantages compared with alginate-based carriers [9][10][11][12]. AOS with lower DPs (2-4) could be used in the field of agricultural production as plant stimulants to promote their growth and development [40][41][42][43], or in the field of biomedicine as signalling molecules to regulate body function [8,44,45].…”
Section: Analysis Of the Enzymatic Hydrolysatementioning
confidence: 99%
“…Recently, research has indicated that AOS could also be used as drug carriers in the development of novel drug delivery systems. AOS rich in M components were used as matrices for posaconazole (POS) delivery, intensifying its antifungal activity [9]. The spherical gel of AOS-containing lysosomes could maintain the activities of lysosomes and prolong its release [10].…”
Section: Introductionmentioning
confidence: 99%